(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
Smoking addiction is one of the major problems that happen to everyone around the world. Many countries have the same problems with their people. Despite all the treatments, advice and warnings from the doctors, media and family, these smokers cannot quit their smoking addiction due to the nicotine addiction in the smoking itself. In addition, smoking has been linked to an increased risk of a wide variety of human diseases, including cancer, heart disease, chronic bronchitis, and chronic obstructive pulmonary disease (COPD). This smoking issue and abuse have been happening for so many years. The purpose of this article is to explain and review more the details about smoking addiction and abuse issues, for instance, causes effects and solutions from the perspective of International, Malaysian and Islamic Law. Through this article, more general knowledge about smoking can be discovered by the analyses from the report, data and surveys from books and the internet. As a consequence, smoking addiction and abuse cannot be ignored and must be considered seriously by people around the world to realize the importance of this issue